Multilingual education in minority-dominated regions in Xinjiang, People’s Republic of China - Zhang, Ping; Adamson, Bob (2020)
Recent developments in multilingualism and multilingual education in minority-dominated regions in China highlight the importance of policy studies to support the national goals of achieving multilingualism (Feng and Adamson, 2015), especially in remote western regions such as Xinjiang Uygur Autonomous Region (XUAR) that pose geographical, socio-political, and educational challenges. This study investigates the effectiveness of language policies and the implementation of multilingual education for minority dominated regions in XUAR, and of the extent to which those policies support multilingual education. The data mainly comprise policy documents issued at the national, regional and institutional level, supplemented by interviews with policy makers at regional and local levels. The study finds that, while the policies at both national and regional levels regarding language education in China are generally supportive of multilingualism, in reality, some of the implemented practices at local school levels in XUAR are not totally consistent with the policy goals, while weak local capacity also hinders the implementation of multilingual education.